Factors involved in the Decision of whether to do or not a Thesis in Psychology Students - Aiquipa, Jesús J. (2018)
Despite the need for scientific research in psychology to solve the different psychosocial problems of the country (family violence and corruption, for example), studies in this area are not still enough. One of the ways to encourage research is by doing a thesis. However, many students opt for other types of jobs for that purpose. The objective of the study is to identify, describe and explain those factors that influence the undergraduate Psychology students’ decision to do or not a thesis in order to obtain the professional degree. A qualitative methodology and the Grounded Theory design were used. We conducted 7 individual interviews and 2 focus groups of a total of 28 university students (20 women and 8 men), living in the city of Lima, 2 of them from public universities and 3 of them from private universities and who were in the last semesters of the Psychology specialty. The results suggest that there are psychological, circumstantial, family, university-related, social and cultural factors, complex interaction of which affects the psychological processes of the student to decide to do or not a thesis, representing the student’s belief system in itself and in relation to the research activity, a main psychological factor.